Productivity in cities: self-selection and sorting (University of Oxford, 2010)
Productivity is high in cities partly because the urban environment acts as a self-selection mechanism. If workers have imperfect information about the quality of workers with whom they match and matches take place within cities, then high-ability workers will choose to live and work in expensive cities. This self-selection improves the quality of matches in such cities. The mechanism may be reinforced by the development of informational networks in cities with a large proportion of high ability workers. As a consequence productivity in these cities is high for workers of all ability types.